Bridging the Gap: From Transactional Culture to Customer-Centric Experience in the B2B Construction Industry - Husam Abu Saida Daw Hasan (Surman Journal of Science and Technology, 2025)
This study investigates the implementation of Customer Experience Management (CXM) within the Business-to-Business (B2B) construction sector—an industry characterized by complex stakeholder networks and traditionally transactional relationships. While CXM is well-established in B2C contexts, its adoption in B2B environments, particularly in construction, remains nascent. Through a qualitative methodology involving an extensive literature review and in-depth semi-structured interviews with ten senior industry professionals, this research maps the generic customer journey and evaluates the applicability and impact of six contemporary CXM strategies. Findings reveal a significant awareness gap and a prevailing transactional culture that hinders customer-centricity. However, strategies like Co-creation, Omnichannel, and Digital Twin are identified as highly impactful. The study concludes that a paradigm shifts towards long-term, trust-based relationships, underpinned by strategic digital transformation and transparent communication, is crucial for successful CXM implementation. This research contributes to the limited academic literature on B2B CXM in construction and provides a validated strategic framework for industry practitioners.